Adsorption of ions and thickness dependence of conductivity in liquid crystals - Kovalchuk, O.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2011)
It is experimentally shown that, at thicknesses less than 100 μm, conductivity
of planar oriented liquid crystals is a function of the thickness. The main reason for this
effect is adsorption of ions on the surface of electrodes. The relation for estimation of
changes in the conductivity has been theoretically obtained, and the value of the
characteristic length for distribution of ions in a near-electrode area has been estimated.